Distinct phenotypic signatures between anejaculation and premature ejaculation: evidence from a large clinical cohort - Zhang, Tianbiao; Shi, Ziang; Wang, Rui; Zheng, Tao; Nan, Yonghao; Lv, Kunlong (Frontiers in Reproductive Health, 2025)
BackgroundAnejaculation (AE) and premature ejaculation (PE) are clinically distinct but mechanistically complex disorders. While both contribute substantially to male sexual health burden, their comparative profiles have not been systematically delineated in large cohorts.MethodsWe retrospectively analyzed 542 men (AE = 249, PE = 293) at a tertiary andrology clinic. All participants underwent vibration perception threshold (VPT) testing at ten standardized sites, spinal MRI reviewed by blinded radiologists, expressed prostatic secretion microscopy with supportive ultrasound for prostatitis, and validated psychological assessments (PHQ-9, GAD-7, SDI-2). Statistical comparisons used Mann–Whitney U tests, chi-squared tests, and multivariate analysis of variance (MANOVA).ResultsAE patients exhibited higher composite VPT thresholds than PE (7.12 ± 1.75 vs. 6.60 ± 1.26, p < 0.001), with MANOVA confirming distinct sensory profiles (Wilks’ λ = 0.907, p < 0.001). Cervical-only abnormalities were markedly more frequent in PE (33.4% vs. 2.8%), whereas AE more often showed either no abnormality (45.8% vs. 28.0%) or combined cervical–lumbar involvement (14.5% vs. 7.5%; overall χ2 = 84.46, p < 0.001). Chronic prostatitis was present in nearly half of AE cases but only one fifth of PE (47.4% vs. 20.1%, p < 0.001). Depressive symptoms were modestly higher in AE (PHQ-9: 8.31 ± 5.96 vs. 7.15 ± 5.65, p = 0.024), while sexual desire and anxiety scores did not differ significantly.ConclusionsAE and PE display distinct clinical signatures. AE was linked to higher vibration thresholds, greater prevalence of prostatitis, and elevated depressive symptoms, while PE was predominantly associated with isolated cervical spine abnormalities. Recognizing these patterns may refine clinical assessment and guide more individualized management.